Secado en lecho fluido de un prototipo granulado a base de la levadura con potencial probiótico Meyerozyma guilliermondii: selección de parámetros de proceso y protector de secado - Chaparro-Rodriguez, Martha Liliana; Cespedes Gutierrez, Elizabeth; Cruz-Barrera, Fredy Mauricio; Castillo Saldarriaga, Carlos; Gomez Alvarez, Martha Isabel (Redalyc, 2024)
Meyerozyma guilliermondii strain Lv196 has been identified as a native Colombian yeast with a high probiotic potential increasing rumen microbial e ciency at in vitro assays when a ruminant digestion system is simulated. Often, these types of products are supplied in a granulated form to facilitate its dosage to ruminants as cows, sheep, among others. To produce granulated bioproducts based on microorganisms, it is required to select suitable drying conditions, protectants and the adequate drying operation, decisive factors to guarantee cell viability and stability during storage. Most granulated products are dried through fluidized bed drying process reducing investment and maintenance costs, and improving mass and heat transfer decreasing operation time and the risk of product overheating. Therefore, in this work a selection of drying protectants through decision matrix was conducted based on parameters as compatibility with Lv196 and cost of protectants. The best two drying protectants were used as functional coadjuvants in the formulation of two granulated prototypes. Drying temperature, chamber pressure and the two prototypes were evaluated in an experimental design to select adequate conditions for a fluidized bed drying process. Finally, the stability of two dried granulated prototypes using selected conditions was determined. Prototype PF2 dried at 45ºC and 0.5 bar during 30 min had a final moisture of 7.84 0.01% and operation yield of 98.54 0.11% guaranteeing a loss of viability lower than 2.09 0.01% after 15 months of storage at room temperature.